Preliminary Study on The Development of An Early Childhood Educational Website for Teaching Materials to Enhance Teaching Skills for Preschool Teachers - Mohamed, Ahmed Abdi; Sunardi; Nur Arifah Drajati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2025)
The teaching skills of preschool teachers in Mogadishu require significant improvement, particularly in adapting to modern educational methodologies. Despite the growing importance of digital resources, many preschool teachers do not integrate or utilize technology during teaching practices. This preliminary study aims to conduct a needs analysis for developing an educational website focused enhancing the teaching skills of preschool teachers. Data collection was conducted through structured and unstructured interviews with 20 preschool teachers from four preschools in Mogadishu, Somalia. Participants were selected using a stratified purposeful sample and categorized by experience: 10 with < 3 years and 10 with > 3 years. This study used the ADDIE model, which includes Analysis, Design, Development, Implementation, and Evaluation. However, this study is limited to analyze stage to identify challenges in teaching materials, technology integration gaps, and the role of educational websites in addressing these needs. The study reveals that preschool teachers in Mogadishu predominantly rely on traditional teaching materials, facing significant gaps in resources, while the integration of educational technology remains limited due to insufficient training, digital skills, and technical support. Teachers expressed a strong need for accessible technology-integrated resources. More than 50% of the interviewed teachers preferred educational website for ready-made materials, though some favored offline e-books due to unreliable internet access. Thus, this study underscores the critical need to develop an educational website to enhance preschool teachers' skills in Mogadishu, addressing gaps in technology integration and access to modern teaching resources.